KEEFEKTIFAN BEBERAPA DOSIS INSEKTISIDA NABATI BABADOTAN (Ageratum conyzoides L.) TERHADAP KUMBANG BUBUK BIJI JAGUNG (Sitophilus zeamais M.) DI PENYIMPANAN - Rahmida Sari; Desita Salbiah (DINAMIKA PERTANIAN, 2020)
ABSTRACT Sitophilus zeamais M. is a storage pest that attacks corn kernels in the storage. Pest control strategies in storage which are often carried out are chemicals, namely insecticides in the form of fumigants. One of them is using plant-based insecticides. Babadotan is a plant that can be used as a botanical insecticide. This research aimed to obtain an effective dose of babadotan flour towards the mortality of S. zeamais pest. This research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, Riau University from March to May 2019. The research was conducted experimentally using a completely randomized design (CRD) with 6 treatments and 4 replications. Treatment given was babadotan flour with the following dosage: Babadotan flour dose 0 g.100 g-1 corn kernels, 2 g.100 g-1 corn kernels, 4 g.100 g-1 corn kernels, 6 g.100 g-1 corn kernels, 8 g.100 g-1 corn kernels, and 10 g.100 g-1 corn kernels. Dose 10 g.100 g-1 babadotan flour corn kernels is an effective dose to control Sitophilus zeamais which can cause total mortality of 82.5% with an initial death of 79,75 hours after application and Lethal time 50 254 hours after application. Application of babadotan flour with a dose of 10 g.100 g-1 corn kernels produced the lowest percentage of corn seed shrinking at 9,55% and resulted in the least individual increase of 4,75 tails. Keywords: Ageratum conyzoides L., Sitophilus zeamais M., Corn